PENGARUH PENDIDIKAN KESEHATAN MELALUI WHATSAPP TERHADAP PENGETAHUAN DAN SIKAP REMAJA KELAS X PADA PENCEGAHAN SEKS PRANIKAH DI SMK NEGERI 5 DENPASAR - Putra, Dewa Gede Wirahadi; Pramitaresthi, I Gusti Ayu; Widyanthari, Desak Made (Coping: Community of Publishing in Nursing; Vol 10 No 4 (2022): Agustus 2022DO - 10.24843/coping.2022.v10.i04.p05, 2022)
Adolescents experience physical and hormonal changes that cause sexual urges to begin. The emergence of sexual urges can trigger adolescents to engage in sexual activities, including premarital sex. Prevention of premarital sex can be done through health education to increase the knowledge and attitudes of the adolescents. Health education through WhatsApp can be used as a medium to disseminate health information to adolescents. This study aimed to determine the effect of health education through WhatsApp on the knowledge and attitudes on the prevention of premarital sex for adolescents at SMK N 5 Denpasar. This study was a pre-experimental with a pretest-posttest one group design. Samples were selected using proportionate stratified random sampling. The sample of this study amounted to 46 people and were given health education messages through WhatsApp regarding the prevention of premarital sex three times a week for two weeks duration. Statistical tests used in this study were the paired t-test and Wilcoxon test. The results of the statistical test showed that there were differences in knowledge (p < 0,001) and attitudes (p = 0,001) before and after the intervention. The provision of health education through WhatsApp affects the knowledge and attitudes of adolescents regarding the prevention of premarital sex in SMK N 5 Denpasar.